Professional insertion of teachers into higher education - Oliveira, Tatiana Pinheiro de; Cruz, Giseli Barreto da (Education Policy Analysis Archives, 2017)
The article presents the results of a research project developed with 15 new entrant teachers between 2012 and 2015 at the Institute of Education of a public university located in the State of Rio de Janeiro. This project aimed to investigate the process of professional insertion and teaching identity construction, as well as to analyze conceptions of teacher education in higher education. The research used a qualitative approach to privilege the understanding of the object from the perspective of the investigated subjects, with a semi-structured interview as the preferred strategy for collecting information. Based on the works of Huberman, Formosinho, Marcelo, Vaillant, Dubar, Pimenta, Almeida, and Anastasiou, aspects related to insertion, teaching identity, institutional culture and formative paths were analyzed. The results show the importance of teacher education policies for the higher education, with special attention to the process of professional insertion in a public institution with exclusive dedication, offering important clues to the elaboration of principles and/or training guidelines for professional induction, through creation, implementation and evaluation of institutional programs to accompany teachers.